Photo-degradation of polyethylene under stress: A successive self-nucleation and annealing (SSA) study. (February 2020) - Liu, Qiang; Liu, Shixiang; Lv, Yadong; Huang, Yajiang; Kong, Miqiu; Yang, Qi; Li, Guangxian
Abstract: Successive self-nucleation and annealing (SSA) technique based on calorimetry is utilized to reveal the effect of uniaxial tensile stress on the photo-oxidation of high density polyethylene (HDPE). Stress-induced acceleratory and inhibitory effects on HDPE are confirmed by analyzing the newly formed melting peaks at low temperatures and the gradually disappeared melting peaks at high temperatures on the SSA curves. The formation of short chains due to chain scission contributes to both the new higher melting peaks (thick lamellae) and lower melting peaks (thin lamellae) because of high mobility and thermodynamic preference, respectively. Besides, chain crosslinking also gives rise to the formation of low melting peaks due to the decrease in the crystallizable sequence lengths and dynamical constraints. Compared with Fourier Transform Infrared Spectrometry, Scanning Electron Microscopy and Small Angle X-ray Scattering, the SSA technique can more precisely and sensitively reflect the early multi-scale aging behavior of HDPE subjected to stress. Highlights: SSA technique reveals the acceleratory and inhibitory effects of tensile stress on the photo-oxidation of HDPE. Chain scission contributes to both the new higher melting peaks and lower melting peaks on SSA curves. SSA technique is superior in detecting the early multi-scale degradation of HDPE under different stress levels.